Africa$1 (Bs power infrastructure : s investment, integration, efficiency - Eberhard, Anton A. (Washington, D.C : World Bank, 2011)
Africa's chronic power problems have escalated in recent years into a crisis affecting 30 countries, taking a heavy toll on economic growth and productivity. The region has inadequate generation capacity, limited electrification, low power consumption, unreliable services, and high costs. It also faces a power sector financing gap on the order of $21 billion a year. It spends only about a quarter of what it needs to spend on power, much of this on operating expenditure required to run the continent's high-cost power systems, leaving little for the huge investments needed to provide a long-term solution.
Includes bibliographical references and index.
1
Keywords: Rural electrification -- Government policy -- Africa, Sub-Saharan.; Energy policy -- Social aspects -- Africa, Sub-Saharan.; Capital investments -- Africa, Sub-Saharan.